2010
DOI: 10.2967/jnumed.109.071407
|View full text |Cite
|
Sign up to set email alerts
|

A Portable γ-Camera for Intraoperative Detection of Sentinel Nodes in the Head and Neck Region

Abstract: We introduced and evaluated a portable g-camera for intraoperative visualization of sentinel nodes in the head and neck region. Methods: Planar lymphoscintigraphy and SPECT/CT were performed after peritumoral injection of 99m Tc-nanocolloid in 25 patients (head and neck melanoma or oral cavity carcinoma). Sentinel nodes were localized intraoperatively with a portable g-camera and a hand-held g-probe. The portable g-camera was used to determine the distribution of remaining radioactivity after excision of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
59
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 14 publications
3
59
0
1
Order By: Relevance
“…Because the probe has a limited spatial resolution and sentinel nodes do not always stain blue, sentinel nodes can be difficult to localize in areas with a complex anatomy and when sentinel nodes are near the injection site (14,15). Although the incorporation of a portable g-camera in the intraoperative procedure partially addresses these limitations by increasing the detection sensitivity and providing an intraoperative overview image of the radioactive sentinel nodes, this device does not depict the surrounding anatomic structures in the surgical field (16)(17)(18).…”
mentioning
confidence: 99%
“…Because the probe has a limited spatial resolution and sentinel nodes do not always stain blue, sentinel nodes can be difficult to localize in areas with a complex anatomy and when sentinel nodes are near the injection site (14,15). Although the incorporation of a portable g-camera in the intraoperative procedure partially addresses these limitations by increasing the detection sensitivity and providing an intraoperative overview image of the radioactive sentinel nodes, this device does not depict the surrounding anatomic structures in the surgical field (16)(17)(18).…”
mentioning
confidence: 99%
“…Prior SPECT images may be mandatory in head and neck cancer, with images from the PGC being used to guide the surgeon and to make sure that the SN has been completely resected. Vermeeren et al [8] have recently reported an improvement of 24% in SN detection. …”
mentioning
confidence: 98%
“…SNs are widely used in breast cancer, melanoma and head and neck cancer, but in the last decade, their use has expanded to additional indications, with more sophistication and complexity in the technique, including indications in urology, gynaecology and gastroenterology. The addition of PGCs has improved the SN technique, particularly when intraoperative tracer injection is needed or in laparoscopic SN localization [7][8][9].In breast cancer, the main indication for a SN procedure worldwide, usually no laparoscopic technique and no intraoperative tracer injection is needed. The utility of the PGC in breast cancer remains only when no conventional gamma camera is available, and in particular in cases with extra-axillary drainage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic (and numeric) feedback generated by a g-ray detection probe (GP) can then be used to provide directional guidance during the intervention (4). Alternatively, portable g-imaging modalities can be used to provide an intraoperative image of the nodal uptake (5,6). Despite research-oriented efforts, commercially available portable g-detection modalities do not yet allow depiction of detailed anatomic information (7,8).…”
mentioning
confidence: 99%